Linking person-job fit to job stress: The mediating effect of perceived person-organization fit - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
Job performance of employees and stress at work are very common problems in today's business world. Many people change their jobs due to high job stress which affects their personal well-being. High stress can be result of incompatibility between the person performing the job and the job's requirements. This can exacerbate feelings of stress on the job and in an employee's personal life. Whilst employees can be reasonably expected to adjust to changes in jobs over time, poor job or employee job fit can result in increased stress and inefficiency in organizations. To combat this we surmise that through careful attention to person-organization fit during the interview or assessment phase, organizations can select employees who are adaptable to change and who can work efficiently to avoid the negative effects of high stress caused by person job incompatibility. In this study we aimed to examine in detail the effects of person-job fit and the importance of person-organization fit in order to allow organizations to prevent the high cost of employees poorly suited to their jobs. The research indicates that organizations whose employees are suited to their jobs operate with greater efficiency and adapt to change more smoothly than those whose employees do not fit their jobs. The study also aims to investigate if perceived person-organization fit mediates the relationship between person-job fit and job stress. The results of the study demonstrate that paying careful attention to person-job fit and adjusting employees to the organization are essential factors for decreasing job stress. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Person-job fit; job stress; person-organization fit; WORK ENGAGEMENT; PERFORMANCE; ANTECEDENTS; EMPLOYEES; VALIDITY; HEALTH; TASK